2019
DOI: 10.3390/agronomy9030133
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Full Straw Incorporation on Soil Fertility and Crop Yield in Rice-Wheat Rotation for Silty Clay Loamy Cropland

Abstract: This 2-year field experiment investigated the effects of full straw incorporation on soil fertility and crop yield in a rice-wheat (Oryza sativa L.–Triticum aestivum L.) rotation on sandy, loamy soil. Two treatments were tested: (i) straw removal (CK) and (ii) straw incorporation (STR). The STR significantly increased the wheat yield by an average of 58% compared with CK; however, no significant difference was found in the rice yield. Soil available nitrogen, phosphorus, and potassium in the 0–20 cm soil layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
62
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(94 citation statements)
references
References 53 publications
(72 reference statements)
13
62
0
3
Order By: Relevance
“…Averaged over 2 years, the straw yield and grain yield under the JM3 treatment were 10.9% and 12.33%, respectively, higher than that without straw (WM0) treatment (Table ). The increase of yield and straw was probably due to increased soil cation exchange capacity and organic carbon at 0–20 cm soil layer . This study confirmed that supply of straw improved grain and straw yield of the maize, which was consistency with the results of Gami et al ., who demonstrated that straw application enhanced sufficient Mg nutrients, increased chlorophyll content, and promoted dry matter accumulation and yield in maize.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Averaged over 2 years, the straw yield and grain yield under the JM3 treatment were 10.9% and 12.33%, respectively, higher than that without straw (WM0) treatment (Table ). The increase of yield and straw was probably due to increased soil cation exchange capacity and organic carbon at 0–20 cm soil layer . This study confirmed that supply of straw improved grain and straw yield of the maize, which was consistency with the results of Gami et al ., who demonstrated that straw application enhanced sufficient Mg nutrients, increased chlorophyll content, and promoted dry matter accumulation and yield in maize.…”
Section: Discussionsupporting
confidence: 92%
“…The increase of yield and straw was probably due to increased soil cation exchange capacity and organic carbon at 0-20 cm soil layer. 74 This study confirmed that supply of straw improved grain and straw yield of the maize, which was consistency with the results of Gami et al, 75 who demonstrated that straw application enhanced sufficient Mg nutrients, increased chlorophyll content, and promoted dry matter accumulation and yield in maize. Therefore, the application of Mg fertilizer with straw return can enhance grain and straw yield in spring maize.…”
Section: Effects Of Mg Application On the Distributions Of Mg In The supporting
confidence: 92%
“…It's called an interactive part of the soil organic component that is mineralized within a couple weeks or months under suitable conditions. The results matched with El-Ghamry et al (2015) and Zhao et al (2019). The organic forms of nitrogen that is present in a form of macromolecules gets slow release to a non-organic form, these plants were higher in soils amendments with compost rice straw alone or in addition to mineral fertilizers.…”
Section: Resultssupporting
confidence: 69%
“…Application of rice straw improves physical characteristics (Bd and Tp). Yang et al (2016) and Zhao et al (2019) mentioned that straw return also can improving the physical characteristics of the soil, such as increased hydraulic conductivity (Hc) and lake of bulk density (Bd).…”
Section: Resultsmentioning
confidence: 99%
“…Positive effect of straw incorporation was also found by Kumari et al (2018) in rice-wheat cropping system. Zhao et al (2019) compared straw removal with straw incorporation in rice-wheat cropping system and found that increase in wheat yield was significant and rice was not significant. Zhao et al (2019) found the positive influence of straw incorporation on soil aggregation and enzyme activities.…”
Section: Results and Discussion Plant Growth And Yieldmentioning
confidence: 99%